A computer program to determine the lateral critical speeds of flexible rotors - Paran, Alexander P. (Philippine Engineering Journal)
This program determines by numerical methods the lateral critical speeds of a rotating shaft of circular cross section and of uniform density. The core of this program uses the method developed independently by Prohl and Myklestad as adapted by J.W. Lund. There is no limit to the number of critical speeds that the program can find, the only requirement being that the shaft in consideration be divided into a sufficient number of sections. The program can handle either English units or the SI and the operator has a choice of entering some values in units of weight or units of mass. Another feature of the program is the ability to plot the mode shapes of the rotor at the different critical speeds.